1993
DOI: 10.1002/bip.360330410
|View full text |Cite
|
Sign up to set email alerts
|

Design of peptides: Crystal and molecular structure of a 310‐helical peptide N‐Boc‐L‐Phe‐dehydro‐Phe‐L‐Val‐L‐Phe‐dehydro‐Phe‐L‐Val‐Och3

Abstract: Highly specific peptide structures can be designed by inserting dehydro residues into peptide sequences. The peptide N-Boc-L-Phe-dehydro-Phe-L-Val-L-Phe-dehydro-Phe-L-Val- OCH3, synthesized by conventional procedures, crystallizes from methanol-water mixtures at 4 degrees C in the tetragonal space group P4(3) with cell parameters a = b = 13.829 +/- 0.003 A, c = 27.587 +/- 0.008 A, V = 5275.5 +/- 0.2 A3, Z = 4, dm = 1.152 +/- 0.005 g cm-3, dcal = 1.150 +/- 0.005 g cm-3. The overall residual factor R = 0.084 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…However, the ⌬ Z Nap residue showed the tendency to form a helical conformation in peptide 2 possessing two ⌬ Z Nap residues, likewise ⌬ Z Phe residues. [47][48][49][50] Conformational energy map computed for Ac-⌬ Z Nap-NMA is shown in Figure 6, which resembles that for Ac-⌬ Z Phe-NMA 31 well. The ⌬ Z Nap residue gave two regions as the stable conformation: one is ( ϳ Ϫ120°, ϳ 20°) corresponding to the (i ϩ 2) residue of type II ␤-turn and the other is ( ϳ Ϫ44°, ϳ Ϫ34°) corresponding to a 3 10 -helix.…”
Section: Solution Conformation Of Peptidementioning
confidence: 96%
“…However, the ⌬ Z Nap residue showed the tendency to form a helical conformation in peptide 2 possessing two ⌬ Z Nap residues, likewise ⌬ Z Phe residues. [47][48][49][50] Conformational energy map computed for Ac-⌬ Z Nap-NMA is shown in Figure 6, which resembles that for Ac-⌬ Z Phe-NMA 31 well. The ⌬ Z Nap residue gave two regions as the stable conformation: one is ( ϳ Ϫ120°, ϳ 20°) corresponding to the (i ϩ 2) residue of type II ␤-turn and the other is ( ϳ Ϫ44°, ϳ Ϫ34°) corresponding to a 3 10 -helix.…”
Section: Solution Conformation Of Peptidementioning
confidence: 96%
“…[24][25][26][27][43][44][45][46][47][48][49][50][51][52][53][54][55] Introduction of these residues into a target sequence promotes or stabilizes a helical structure (usually, 3 10 -helix). [24][25][26][27][43][44][45][46][47][48][49][50][51][52][53][54][55] Achiral peptides composed mainly of (D Z Phe-Aib) units, including peptide 2, were found to adopt 3 10 -helix in solution [14][15][16][17][18][19] and in crystal states. 56,57 Theoretical study also supports that the (D Z Phe-Aib)-based periodic sequence has a propensity to take a helical form.…”
Section: Helical Conformation Of Peptidementioning
confidence: 99%
“…It has been found that in the solid state a ∆Phe residue of the Z configuration induces β-turns in short sequences [2][3][4][5][6] and a 3 10 -helix in longer ones or peptides with more than one dehydro residue. 4,[7][8][9][10][11][12][13][14][15][16][17][18][19] Similar conformational properties of ∆ Z Phe have been observed in solution by NMR 8,11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and CD, 18,19,[27][28][29][30][31][32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 67%